Clinicopathological overlap of neurodegenerative diseases: A comprehensive review. (August 2020) - Das, Sumit; Zhang, Zach; Ang, Lee Cyn
Highlights: Patient may have pathological features of two or more neurodegenerative disorders. Important to recognize of overlapping pathology to prevent missed diagnoses. Shared pathogenetic mechanisms and genetic signatures between some disorders. May need to re-examine traditional classification of neurodegenerative disorders. Abstract: Clinical and neuropathological overlap of two or more neurodegenerative diseases (ND) is not an uncommon occurrence yet is still underdiagnosed in clinical neurological and neuropathological. The authors present a clinicopathological overview of the current understanding of overlapping ND's with the hope that this review will encourage further studies that are required to investigate the effect of such overlaps on clinical presentations and how often clinical presentations raise the suspicion of multiple ND's. The authors suggest that as more patients with overlapping ND's come to light, traditional classification system of ND's may need to be modified.